Orientalism in celluloid: the production of the ‘crazy year’ / Thery Beord and Achim Alan Merlo - Beord, Thery; Alan Merlo, Achim (Penerbit UiTM (UiTM Press), 2017)
This article introduces a journey in the orientalist movement that characterises the cinema of the ‘crazy years’ between 1919 and 1929. Attention will be turned on the peculiarities of this period, including the socio-cultural dimension of that epoch. The role of the woman in cinematographic art will be considered as an appropriate tool for the interpretation of orientalism in the European society during the interwar period. Period of the creation of a popular culture or popularisation of culture, Orientalism became a mean to escape with fantasy the everyday way of life of modern European society. The film directors involved in the new emerging art, cinema for instance, included Orientalism into their scripts as an artistic style which was already extensively developed in painting and literature beforehand. This process leads to the trivialisation of Orientalism in the collective imagination and to the estrangement of the more ethnographic documentary films with the fictional treatments. We introduce here in this article some significant achievements proceeding from this estrangement. Finally a comparative look will be granted to the French-German couple, core of the European building, with the example of the Atlantis myth, revisited with an Orientalist vision.